Determinan Minat Financing UMKM Pada Lembaga Keuangan Syariah (Studi Kasus UMKM Disekitar Malioboro Yogyakarta) - Ayif Fathurrahman (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze the determinants of Micro, Small and Medium Enterprises (MSMEs) interest in conducting the financing from Islamic Financial Institutions and to find out what factors are the most dominant influence on MSMEs interest in applying for financing at Islamic financial institutions. The data used in this study is primary data. The subject of this research is the owner of MSMEs around Malioboro Yogyakarta. In this study using a sample of 100 respondents. The sampling technique is using the Non Probability Sampling technique by means of Purposive Sampling. The data collection method used a questionnaire with a Likert scale. The analytical tool used is multiple regression which is supported by SPSS 16 software. Based on the analysis conducted, the results show that service, reputation and procedure variables have a positive and significant influence on interest